The Globalized Model of the Past: A Qualitative Comparative Study of the Official Memory Policies in Chile and Colombia; [el Modelo Globalizado del Pasado Un Estudio Comparativo Cualitativo de Las Políticas Oficiales de Memoria en Chile y Colombia] - Prosser-Bravo, G (Centro de Investigacion y Docencia Economicas A.C., 2024)
Reparations policies within the framework of transitional justice, as implemented by Chile and Colombia, serve as mechanisms for addressing the harm inflicted upon victims. This paper explores the construction of the memory concept within official reparations policies in these two countries. The methodology used was a transnational comparative analysis, developed through a content analysis to examine the formulation of memory in official reparation policies. The findings reveal a prescriptive global memory model characterized by four key aspects: the interplay between memory and official truth, memory institutions, the role of archives, and commemorative practices. The study concludes that despite historical differences, Chile and Colombia exhibit strikingly similar approaches in addressing their violent pasts through a prescriptive global memory model within transitional justice. © 2024, Centro de Investigacion y Docencia Economicas A.C.. All rights reserved.
Keywords: reparations policies; memory politics; transnational comparative analysis; global memory model; social psychology